Asiaticoside Attenuates Cell Growth Inhibition and Apoptosis Induced by Aβ1-42 via Inhibiting the TLR4/NF-κB Signaling Pathway in Human Brain Microvascular Endothelial Cells - Song, Daqiang; Jiang, Xian; Liu, Yiliu; Sun, Yuhong; Cao, Shousong; Zhang, Zhuo (Frontiers in Pharmacology, 2018)
Alzheimer`s disease (AD) is a very common progressive neurodegenerative disorder with the highest incidence in the world. Dysfunction of the blood brain barrier (BBB) may be responsible for the pathogenesis and pathology of AD for abnormally transporting amyloid-β (Aβ, the main component of the senile plaques) from the sera into the central nervous system. Aβ peptides induce apoptosis in human brain microvascular endothelial cells (hBMECs), the main component of BBB. Apoptosis in neuronal cells plays a critical role in the pathogenesis of AD. Asiaticoside, a natural glycoside extracted from Centella asiatica (L.) Urban, has an anti-apoptotic effect on hBMECs but the molecule mechanism remains unclear. Therefore, we investigate the protective effect of asiaticoside on Aβ1-42-induced cytotoxicity and apoptosis as well as associated mechanism in hBMECs with commonly used in vitro methods for clinical development of asiaticoside as a novel anti-AD agent. In the present study, we investigated the effects of asiaticoside on cytotoxicity by Cell Counting Kit-8 assay, mitochondrial membrane potential by JC-1 fluorescence analysis, anti-apoptosis by Hoechst 33258 staining and Annexin V-FITC (fluorescein isothiocyanate) and propidium iodide (PI) analyses, the expressions of TNF-α and IL-6 by enzyme-linked immunosorbent assay (ELISA) and TLR4, MyD88, TRAF6, p-NF-κB p65, and total NF-κB p65 by Western blotting, and nuclear translocation of NF-κB p65 by immunofluorescence analysis in hBMECs. The results showed that pretreatment of asiaticoside (25, 50, and 100 μM) for 12 h significantly attenuated cell growth inhibition and apoptosis, and restored declined mitochondrial membrane potential induced by Aβ1-42 (50 μM) in hBMECs. Asiaticoside also significantly down-regulated the elevated expressions of TNF-α, IL-6, TLR4, MyD88, TRAF6, and p-NF-κB p65, as well as inhibited NF-κB p65 translocation from cytoplasm to nucleus induced by Aβ1-42 in hBMECs in a concentration-dependent manner. The possible underlying molecular mechanism of asiaticoside may be through inhibiting the TLR4/NF-KB signaling pathway. Therefore, asiaticoside may be developed as a novel agent for the prevention and/or treatment of AD clinically.